Stability, accuracy, and clinical performance of enzymatic total CO₂ measurement: Evaluation of the Snibe and Roche assays - Shuai Wei; Zhonggang Fang; Min Shi; Qunxian Zhang; Qiang Huang; Gao Chen; Zhenlei Wei; Chen Sun; Haolin Wei; Tinghua Li; Chen Lan (PLoS ONE, 2025)
Objectives To evaluate the stability, accuracy, and clinical performance of the Snibe CO₂ assay compared with the Roche CO₂ reagent and to investigate factors affecting total CO₂ measurements in different clinical conditions. Methods Total CO₂ was measured in patient samples using enzymatic assays. Stability was assessed over time, and CO₂ loss was examined in different blood collection tubes. Method comparison was conducted between the Snibe and the Roche CO₂ assays in various diseases. Results The Snibe CO₂ assay showed excellent linearity (r = 0.9997) and maintained stability for 42 days without recalibration, with control material deviations within ±5% of the target. CO₂ loss was observed in uncapped non-anticoagulant tubes (24.0% decline over 48 hours), but was less in EP tubes (9.4% decline). Significant differences of median CO₂ measurements were observed in only the renal group (Snibe: 13.35 mmol/L, Roche: 12.80 mmol/L) and the cardiovascular disease group (Snibe: 25.90 mmol/L, Roche: 26.40 mmol/L) versus the healthy group (Snibe: 22.70 mmol/L, Roche: 22.90 mmol/L) for both the Snibe and Roche assays. Conclusions The Snibe CO₂ assay demonstrated superior stability and comparable accuracy compared with the Roche reagent. Preanalytical CO₂ loss remains a critical issue, emphasizing the need for standardized sample handling. Given the correlation between total CO₂ and bicarbonate levels, accurate measurement is critical for diagnosing metabolic disorders. Laboratories should establish protocols to minimize errors and ensure reliable acid-base assessment in clinical practice.